Advancing onset of breeding dates in brood parasitic common cuckoos and their great reed warbler hosts over a 22-year period. Issue 5 (3rd September 2021) - Hauber, Márk E.; Elek, Zoltán; Moskát, Csaba
Abstract : Ongoing global change has had biologically impactful effects on the breeding phenology of both resident and migratory bird species, including avian hosts and their obligate brood parasites. We analyzed a local breeding site's weather changes in Central Hungary and shifts in the reproductive timing of two interacting long-distance migratory bird species in a 22-year-long data set. Some weather and all of our breeding phenology metrics of host great reed warblers Acrocephalus arundinaceus and obligate brood parasitic common cuckoos Cuculus canorus showed strong statistical patterns, with spring temperatures increasing and host and parasite laying dates becoming earlier with advancing years. However, temporally decoupled weather metrics did not consistently predict host or brood parasitic reproductive onsets. This suggests that breeding site weather change does not cause the ongoing advancement in the reproductive timing of these avian hosts and their brood parasites.